The Beta Adrenergic Receptor Blocker Propranolol Counteracts Retinal Dysfunction in a Mouse Model of Oxygen Induced Retinopathy: Restoring the Balance between Apoptosis and Autophagy - Cammalleri, Maurizio; Locri, Filippo; Catalani, Elisabetta; Filippi, Luca; Cervia, Davide; Dal Monte, Massimo; Bagnoli, Paola (Frontiers in Cellular Neuroscience, 2017)
In a mouse model of oxygen induced retinopathy (OIR), beta adrenergic receptor (BAR) blockade has been shown to recover hypoxia-associated retinal damages. Although the adrenergic signalling is an important regulator of apoptotic and autophagic processes, the role of BARs in retinal cell death remains to be elucidated. The present study was aimed at investigating whether ameliorative effects of BAR blockers may occur through their coordinated action on apoptosis and autophagy. To this aim, retinas from control and OIR mice untreated or treated with propranolol, a non-selective BAR1/2 blocker, were characterized in terms of expression and localization of apoptosis and autophagy markers. The effects of propranolol on autophagy signalling were also evaluated and specific autophagy modulators were used to get functional information on the autophagic effects of BAR antagonism. Finally, propranolol effects on neurodegenerative processes were associated to an electrophysiological investigation of retinal function by recording electroretinogram (ERG). We found that retinas of OIR mice are characterized by increased apoptosis and decreased autophagy, while propranolol reduces apoptosis and stimulates autophagy. In particular, propranolol triggers autophagosome formation in bipolar, amacrine and ganglion cells that are committed to die by apoptosis in response to hypoxia. Also our data argue that propranolol, through the inhibition of the Akt-mammalian target of rapamycin pathway, activates autophagy which decreases retinal cell death. At the functional level, propranolol recovers dysfunctional ERG by recovering the amplitude of a- and b-waves, and oscillatory potentials, thus indicating an efficient restoring of retinal transduction. Overall, our results demonstrate that BAR1/2 receptors are key regulators of retinal apoptosis/autophagy, and that BAR1/2 blockade leads to autophagy-mediated neuroprotection. Reinstating the balance between apoptotic and autophagic machines may therefore be viewed as a future goal in the treatment of retinopathies.